(untitled) (Damu Journal of Sport Sciences, 2025)
The objectives of the research were demonstrated by preparing compound exercises using a play and competitive style, identifying the effect of compound exercises using a play and competitive style on developing some basic skills in under-19 football, and identifying the differences between the experimental and control groups in developing some basic skills in under-19 football. As for the research methodology, the researcher used the experimental method using equal groups (experimental, control) with pre- and post-tests. The research population and sample were determined as young football players under the age of 19 at Karbala Sports Club for the 2024-2025 season, totaling (26). Player, where each group consisted of (13) players, and the data were presented, analyzed, discussed and processed statistically using the statistical package SPSS, and through the results, the researcher reached several conclusions that the nature of the exercises that were prepared are compatible with the capabilities of young players under 19 years of age, which led to the development of basic skills in football, and that the use of complex exercises in the style of play and competition within the training curriculum in the special preparation stage had a positive impact in developing basic skills in football.